STRATEGI BRANDING RUMAH SAKIT DALAM MENINGKATKAN KEPERCAYAAN DAN LOYALITAS PASIEN - Hotmaria Hertawaty Sijabat (CV. ADIBA AISHA AMIRA, 2026)
This article discusses hospital branding strategies aimed at enhancing patient trust and loyalty. Amid increasingly fierce competition in the healthcare sector, hospitals are required not only to provide high-quality medical care but also to build a credible, professional and patient-centred image. Strong branding is a key factor influencing public perception of the quality of hospital services. Through consistent, transparent and human-centred branding, hospitals can instil a sense of security and confidence in patients when choosing healthcare services. This article is based on a literature review, examining various sources relating to hospital branding, patient trust and patient loyalty. The findings indicate that patient trust is built through consistent service quality, clear communication, a good reputation and positive service experiences. Furthermore, this trust forms the basis for patient loyalty, which is reflected in the willingness to use the hospital’s services again and to recommend them to others. Thus, hospital branding serves not only as a promotional tool but also as a long-term strategy to strengthen the relationship between the hospital and its patients.